Impact of exposure to Covid-19 related News on the sensation of fear among Brazilians (Revista Eixos Tech, 2024)
Seventeen months after the decree of the COVID-19 pandemic and in a scenario of greater certainty and knowledge about the disease and its behavior, a survey was carried out with the objective of investigating the Impact of exposure to Covid-19 related News on the sensation of fear among Brazilians. For that, a self-administered electronic questionnaire was applied to 246 social network users selected through the snowball method. Data interpretation was performed using descriptive statistics and the use of a correlation matrix. The results pointed to a significant relationship between nervousness and anxiety when hearing news about COVID-19 and the physical and psychological sensations of fear Fear of COVID-19, Discomfort when thinking about COVID-19 and Fear of die from COVID-19 is in line with other research. Contrary to the academic literature, a significant reference to Sleep trouble from worry about contracting COVID-19 was not found in this study. In this study, questions were not asked about the influence of different means of communication in this process or the role of moderators such as gender and age, gender or age, being this information (at the same time) limitations of this work and suggestions for future studies . Because it was conducted seventeen months after the pandemic was declared, the results reflect the consequences of prolonged and frequent exposure to the subject.